Nanoparticles for the Induction of Antigen-Specific Immunological Tolerance - Kishimoto, Takashi Kei; Maldonado, Roberto A. (Frontiers in Immunology, 2018)
Antigen-specific immune tolerance has been a long-standing goal for immunotherapy for the treatment of autoimmune diseases and allergies and for the prevention of allograft rejection and anti-drug antibodies directed against biologic therapies. Nanoparticles have emerged as powerful tools to initiate and modulate immune responses due to their inherent capacity to target antigen presenting cells (APCs) and deliver coordinated signals that can elicit an antigen-specific immune response. A wide range of strategies have been described to create tolerogenic NPs (tNPs) that fall into three broad categories. One strategy includes tNPs that provide antigen alone to harness natural tolerogenic processes and environments, such as presentation of antigen in the absence of co-stimulatory signals, oral tolerance, the tolerogenic environment of the liver, and apoptotic cell death. A second strategy includes tNPs that carry antigen and simultaneously target tolerogenic receptors, such as pro-tolerogenic cytokine receptors, aryl hydrocarbon receptor (AHR), FAS receptor, and the CD22 inhibitory receptor. A third strategy includes tNPs that carry a payload of tolerogenic pharmacological agents that can “lock” APCs into a developmental or metabolic state that favors tolerogenic presentation of antigens. These diverse strategies have led to the development of tNPs that are capable of inducing antigen-specific immunological tolerance, not just immunosuppression, in animal models. These novel tolerogenic nanoparticle technologies heralds a promising approach to specifically prevent and treat unwanted immune reactions in humans. The first tNP, SEL-212, a biodegradable synthetic vaccine particle encapsulating rapamycin (SVP-Rapamycin), has reached the clinic and is currently in Phase 2 clinical trials.